2003
DOI: 10.1152/ajpheart.00731.2002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor blockade has an oxygen-saving effect in Dahl salt-sensitive rats with heart failure

Abstract: . Endothelin receptor blockade has an oxygen-saving effect in Dahl salt-sensitive rats with heart failure. Am J Physiol Heart Circ Physiol 285: H1428-H1434, 2003. First published June 5, 2003 10.1152/ ajpheart.00731.2002The effects of endothelin (ET) receptor blockade on energy utilization in heart failure (HF) are unknown. We administered ET type A (ET A), ET type B (ET B), and ETA/ETB antagonists to isolated hearts from Dahl salt-sensitive (DS) rats with HF and controls. Contractile efficiency was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…A similar finding was reported in chronic tachycardia heart failure in dogs [70]. Economy and efficiency are also increased in Dahl salt sensitive rats with chronic left ventricular dilatation and reduced shortening fraction due to severe, salt-induced hypertension [16].…”
Section: Functional Consequences Of Sarcomeric Protein Modification Isupporting
confidence: 80%
See 4 more Smart Citations
“…A similar finding was reported in chronic tachycardia heart failure in dogs [70]. Economy and efficiency are also increased in Dahl salt sensitive rats with chronic left ventricular dilatation and reduced shortening fraction due to severe, salt-induced hypertension [16].…”
Section: Functional Consequences Of Sarcomeric Protein Modification Isupporting
confidence: 80%
“…However, the mechanism(s) is uncertain. In Dahl rats, we have shown that the mechanoenergetic alterations of the contractile machinery are largely reversible with acute endothelin A but not B receptor blockade [70]. This suggests a role for PKC signaling, since the latter is a key downstream effector of endothelin receptor activation.…”
Section: Functional Consequences Of Sarcomeric Protein Modification Imentioning
confidence: 84%
See 3 more Smart Citations